Perhitungan Harga Pokok Penjualan Pada UMKM di Cikarang: Studi Kasus Mie Ayam Bakso Sragen Mas Pri - Muhamad Syahwildan; Tutiek Indriani; Abel Nabila; Wini Nur Optaviani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study highlights the importance of accurately calculating the Cost of Goods Sold (COGS) as a foundation for strategic decision-making in the operations of Micro, Small, and Medium Enterprises (MSMEs), specifically focusing on the business